Beethoven Festival concert of the Société Philharmonique de Bruxelles and the Concerts Populaires conducted by Erich Kleiber, March 18-19, 1933 (Brussels; Belgium, 2020)
Program for the third Beethoven Festival concert by the Orchestre Symphonique de Bruxelles directed by Erich Kleiber on March 18-19, 1933, that included performances of the Coriolan Overture, Symphony no. 4, and Symphony no. 5. With program notes in French.